Faculty of Industrial Sciences and Technology undergraduate final year project module - Ahmad Zamani, Ab Halim; Hong, Pui Khoon; Rasidi, Roslan; Ros Azlinawati, Ramli; Mirta, Widia; Kamrul Fakir, Kamarudin; Noor Diana, Abdul Majid; Nurjannah, Salim; Nor Ashikin, Sopian; Nurliyana, Moh Hussin (Penerbit UMPSA, 2025)
This module serves as a guide and activity log for final year undergraduate students from the Faculty of Industrial Sciences and Technology (FIST) in completing their final year project (FYP) within two semesters. The module consists of three sections: FYP guidelines, weekly activity logs and a list of evaluation forms. The easy-to-use weekly activity log enables students to organise and prioritise their research activities, as well as to maintain a complete documentation for research. Ultimately, we hope this module can help students to work efficiently and produce quality thesis.